“Arch Macedonia”, from Pseudo Classicism to Monument of Culture, from Political Ritualization to Civil Demystification - Ристески, Љупчо С. (Poznańskie Studia Slawistyczne, 2017)
In this paper, we are considering the social aspects of the object “Porta Macedonia” as a part of the project “Skopje 2014”, its political and cultural meanings, its symbolic aspects and its reflection on identity policies in contemporary Macedonia. We read buildings and monuments of “Skopje 2014” project as texts, interpret them as symbols recognizing as signs of multilayered ideas and interpretations of the nation under strong political patronage. The text shows how a monument in a very short period creates multiple layers of symbolism which, depending on social contexts, can be read in different ways.